Quick identification of Type I restriction enzyme isoschizomers using newly developed pTypeI and reference plasmids - Ryu, Junichi (Oxford University Press, 2008)
Although DNA-recognition sequences are among the most important characteristics of restriction enzymes and their corresponding methylases, determination of the recognition sequence of a Type-I restriction enzyme is a complicated procedure. To facilitate this process we have previously developed plasmid R-M tests and the computer program RM search. To specifically identify Type-I isoschizomers, we engineered a pUC19 derivative plasmid, pTypeI, which contains all of the 27 Type-I recognition sequences in a 248-bp DNA fragment. Furthermore, a series of 27 plasmids (designated ‘reference plasmids’), each containing a unique Type-I recognition sequence, were also constructed using pMECA, a derivative of pUC vectors. In this study, we tried those vectors on 108 clinical E. coli strains and found that 48 strains produced isoschizomers of Type I enzymes. A detailed study of 26 strains using these ‘reference plasmids’ revealed that they produce seven different isoschizomers of the prototypes: EcoAI, EcoBI, EcoKI, Eco377I, Eco646I, Eco777I and Eco826I. One strain EC1344 produces two Type I enzymes (EcoKI and Eco377I).